Tubuan and tabernacle the life stories of two priests of Papua New Guinea : the Most Reverened Benedict To Varpin, CBE Archbishop Emeritus : Reverend Father Bernard Franke MSC, CBE Missionary in New Britain - Mennis, Mary, 1938-; Catholic Mission (Vunapope, Papua New Guinea) (Aspley, Qld. : Lalong Enterprises, 2007)
2007 is the 125th anniversary of the Sacred Heart Missionaries in New Britain. The history of the Mission and the traditional culture and beliefs of the Tolai people provide the background for this book. The book is about two priests: one a German and the other a Papua New Guinea from the Rabaul area of New Britain. Fr Bernard Franke arrived from Germany in 1928 when he was 26 years old, full of missionary zeal and spent the following 50 years in New Britain. Archbishop Benedict To Varpin, grew up in the Tolai society with all the traditional tribal customs.
Includes index.
Bibliography: p. 275-278.
Keywords: To Varpin, Benedict, -- 1936-; Franke, Bernard, -- 1903-1984.; Missionaries -- Papua New Guinea -- Biography; Missionaries -- Germany -- Biography; Missions -- Papua New Guinea -- New Britain Island -- History; Papua New Guinea -- Biography